Perancangan Bangun Sistem Kontrol Proses pada Alat Pengeringan Biji Kakao - Ira Dwitasari; Ahmad Radhy; Putu Eka Widya Pratama; Murry Raditya; Hagai Yemima (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2025)
The growth in cocoa production in Indonesia is not matched by its quality, where the drying process is a crucial parameter that must be controlled. Excessively high drying temperatures tend to negatively impact the beans, resulting in a sour aroma, and the beans can become charred. The moisture content in cocoa beans needs to be reduced to a maximum of 7.5% to produce quality cocoa beans. This research developed the creation of a cocoa bean drying box with a drying process control system, temperature and humidity monitoring by the SHT20 sensor. There is a DS18B20 sensor to measure the temperature of the cocoa beans during drying. Two microcontrollers are used: STM32 as a control and displays sensor readings on the LCD, and ESP32 connected to the STM32 to send data to the dashboard and database. The drying process utilizes a heater as a heating element until the temperature reading on the SHT20 sensor is ≤ 55°C. When the heater is inactive, a fan will be active to lower the drying temperature to maintain the drying process at an optimal temperature and prevent damage to the cocoa beans. The results of testing the cocoa bean drying process for 24 hours with data collection every 1 hour, where real-time data is stored in the online dashboard, obtained the average temperature of the drying box room is 51°C, the average temperature of the cocoa beans is 42°C, and the average moisture content of the cocoa beans is 7.5%.